"Bringing Down the Flag": Removing the Contact Precautions Label for Non-hospitalized Patients with Prior Methicillin-Resistant Staphylococcus aureus Infection or Colonization. (28th January 2015) - Carson, Paul J.; Danford, Mallory; Carson, Grace; Hanish, Christine; Thompson, Jody; Orr, Megan; Traynor, Michael; Roth, Felix; Guerrero, Dubert
<x content-type="archive" xml:space="preserve">Abstract</x> A policy consensus has not been reached regarding discontinuing contact precautions in patients with a history of methicillin-resistant Staphylococcus aureus (MRSA). We found that as many as 72% of outpatients flagged for past MRSA were no longer carriers, and a single nasal PCR test provided a reasonable negative predictive value for removing contact precautions. Infect Control Hosp Epidemiol 2015;00(0): 1–3